Restrukturisasi Perguruan Tinggi Swasta Sebagai Upaya Penyehatan Dan Peningkatan Kualitas Institusi - Cita Yustisia Serfiyani (Jurnal Hukum IUS QUIA IUSTUM, 2020)
The quantity of private universities in Indonesia that is not comparable with the fulfillment of higher education quality standards and the low quality of graduates is an important issue. Efforts to streamline the number of private universities can be pursued by restructuring legal entities, by means of mergers, consolidations, acquisitions and company separation which are of course adjusted to the character of foundations and private universities. Restructurisation is still experiencing problems that it is necessary to analyse the inhibiting and the supporting factors. This research aims to first, analyse the arrangements of legal protection for the restructurisation of private tertiary institutions, both between foundations and private tertiary institutions; second, formulating a method of restructuring private tertiary institutions that is appropriate for institutional restructurisation. This normative juridical research concludes that arrangements regarding obligation of restructurisation and the transfer of rights and obligations of the parties, first, both in restructurisation among foundations and restructurisation among private universities, need to be clarified in order to provide legal protection for the parties and the successful management of post-restructurised entities. Second, the appropriate restructurisation method to be applied is mergers and consolidations which must be supported by a new set of regulations that provide opportunities and obligation of restructurisation for private universities with certain indicators.